Intensitas Serangan Semut pada Tanaman Buah Naga (Hylocereus sp.) di Kota Pariaman, Sumatera Barat - Halimah Tus Sakdiah; Henny Herwina; Mairawita Mairawita (Universitas Andalas, 2015)
A study about the intensity attact of ant in dragon fruit (Hylocereus sp.) plantation was conducted on September 2015 in Pariaman City, West Sumatera. The ants were collected by using free collection method with purposive sampling techniques. About 10% of the dragon fruit plant in the study location was observed.The result showed that theintensity attack on dragon fruit was caused by fire ant Solenopsis geminata(25%).